Comparative Analysis of Tiktok Marketing based on Buyer and Seller Perceptions - Heppy Agustiana Vidyastuti (Research Synergy Foundation, 2024)
The purpose of this study was to examine the perceptions of buyers and sellers in Bandung regarding the use of TikTok for marketing. This study used a quantitative approach with descriptive methodology, involving 100 buyers and 100 sellers as respondents. The questionnaire was used as a research instrument and accidental sampling technique. The findings of this study: 1. Sellers showed high enthusiasm for five of the six dimensions of benefits obtained from using TikTok marketing. 2. Sellers showed more enthusiasm than buyers for context, communication, collaboration, and connection. 3. Sellers’ perceptions of the benefits of TikTok marketing surpassed buyers. 4. In social media marketing, sellers showed a much higher level of enthusiasm than buyers. 5. Of the six dimensions of social media marketing content, sellers outperformed buyers. 6. The seller's perception of the dimensions that must be evaluated from TikTok's marketing content is superior to the Buyer's perception.